Renal angiotensin-converting enzyme is essential for the hypertension induced by nitric oxide synthesis inhibition - Giani, Jorge Fernando (2014)
The kidney is an important source of angiotensin-converting enzyme (ACE) in many species, including humans. However, the specific effects of local ACE on renal function and, by extension, BP control are not completely understood. We previously showed that mice lacking renal ACE, are resistant to the hypertension induced by angiotensin II infusion. Here, we examined the responses of these mice to the low-systemic angiotensin II hypertensive model of nitric oxide synthesis inhibition with L-NAME. In contrast to wild-type mice, mice without renal ACE did not develop hypertension, had lower renal angiotensin II levels, and enhanced natriuresis in response to L-NAME. During L-NAME treatment, the absence of renal ACE was associated with blunted GFR responses; greater reductions in abundance of proximal tubule Na+/H+ exchanger 3, Na+/Pi co-transporter 2, phosphorylated Na+/K+/Cl- cotransporter, and phosphorylated Na+/Cl- cotransporter; and greater reductions in abundance and processing of the γ isoform of the epithelial Na+ channel. In summary, the presence of ACE in renal tissue facilitates angiotensin II accumulation, GFR reductions, and changes in the expression levels and post-translational modification of sodium transporters that are obligatory for sodium retention and hypertension in response to nitric oxide synthesis inhibition.